Magnetically Enhanced Ultrasound Strain Elastography to Visualize Magnetic Nanoparticles - Huber, Christian; Müller, Melina Sophie; Ermert, Helmut; Heim, Christian; Rupitsch, Stefan J.; Ullmann, Ingrid; Lyer, Stefan (22. GMA/ITG-Fachtagung Sensoren und Messsysteme 2024, 2024)
This study explores the potential of Magnetically Enhanced Ultrasound Strain Elastography (MUSE) for visualizing the distribution of magnetic nanoparticles (MNPs) employed in magnetic drug targeting (MDT). MDT leverages MNPs as drug carriers, accumulated by an external magnetic field at the target site, typically a tumor. The localized accumulation of these particles alters the effective elastic properties of the tissue, potentially enabling visualization through ultrasound strain imaging, which maps local variations in elasticity. However, a direct link between MNPs and regions of increased stiffness has yet to be established. This work proposes MUSE as a solution, utilizing an external magnetic field to manipulate MNP distribution and consequently, tissue elasticity. The feasibility of MUSE was assessed using a polyvinyl alcohol ultrasound phantom containing an MNP inclusion. The results demonstrated successful mapping of the inclusion using the proposed metho
Keywords: Medical Technology; Ultrasound Imaging; Cancer Therapy; Magnetic Nanoparticles; Magnetic Durg Targeting